(untitled) (Castilla. Estudios de Literatura, 2022)
In this paper we delve into the functions of the classical Greco-Roman referents in the work of the Mexican writer Rosario Castellanos (1925-1974). Through the analysis of decisive texts for this topic, we demonstrate that the educated references acquire relevance to discover their denunciation of the marginality of women, which is achieved through the revision of tradition and the ironic vision that demystifies feminine stereotypes, like that of the woman in love, the family woman or the famous writer. The lack of global studies on this issue and their interest in knowing the work of Castellanos justify our contribution.